TEKNOLOGI GELATINISASI PADA PAKAN SUMBER ENERGI DAN SUPLEMENTASI ASAM AMINO SEBAGAI UPAYA OPTIMALISASI PERTUMBUHAN TERNAK RUMINANSIA - Susi Dwi Widyawati (Universitas Sebelas Maret, 2010)
The study aimed to determine the effect of gelatinisation of feed ingredients as a energy sources by steaming and amino acid supplementation and its use in rations of sheep on performance improvements, has been done in the cage experiment Jatikuwung, Department of Animal Husbandry UNS for 4 (four) months, starting from June until September 2009. Analysis of feed materials is done in laboratory of Nutrition and Feed Science, Faculty of Agriculture UNS. Twenty sheeps with the initial's body weight ranged from 10 + 0.4 kg, were divided randomly into 6 treatments. The rations consisted of king grass and concentrate with the ratio = 60: 40 (DM basis). Treatment applied is P1: rice bran, P2: steamed rice bran, P3: steamed rice bran + MHA, P4: Onggok, P5: Onggok steamed and Q6: Onggok steamed + MHA. Each treatment is repeated 4 times and each test consisted of one sheep. Anova is used to determine the effect of treatment variables were observed and DMRT to test the real difference between treatments. The results showed that steaming and MHA supplementation did not affect the consumption of rations, ADG and FCR, this situation illustrates that the treatment can not be applied to improve the consumption, resulting in an PBBH, although there is a tendency to increase consumption and PBBH especially in rice bran. But the real protein consumption (P <0.05) influenced by treatment. The protein consumption is higher of Rice bran (P <0.05) compared onggok. Decrease in protein consumption significantly (P <0.05) followed by PBBH trend, this shows an improvement of protein quality steaming and supplemented with MHA so that there is also a tendency increase protein efficiency ration. Steaming rice bran and supplemented MHA and its use in rations provide a good influence on growth and protein quality of sheep rations.